KEMAMPUAN PERGANTIAN AUDITOR DAN PRIOR OPINION MEMODERASI PENGARUH POTENSI FINANCIAL DISTRESS TERHADAP OPINI GOING CONCERN - Putri, Putu Yudha Asteria; Astika, Ida Bagus Putra; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aimed to get empirical evidence the auditor's ability to change and prior opinion in moderating influence on the potential financial distress Award going concern opinion. There’s a going concern opinion because the company indicated no longer able to carry out its life. The results of previous studies get inconsistent results in terms of the potential influence on the provision of financial distress going concern opinion. The existence of a contingency approach can be completed in this study, where the variables change of auditor and prior opinion allegedly moderating influence on the potential financial distress Award going concern opinion. This study uses secondary data. Manufacturing companies listed in Indonesia Stock Exchange period 2009-2015 the population in this study by the amount total of the samples are 77 samples were selected by purposive sampling.
Keywords: going concern opinion, financial distress, prior opinion, auditor switching